Status Hara Nitrogen, Fosfor, Kalium dan Tingkat Kesuburan Tanah Pada Tiga Penggunaan Lahan Berbeda di Kecamatan Dolo Kabupaten Sigi - Lisa, Lisa; Basir, Muhammad; Hasanah, Uswah (Mitra Sains, 2022)
This research was conducted to determine nutrient status and soil fertility levels in Dolo District, Sigi Regency, map the soil nutrient status and soil fertility levels in Dolo District, Sigi Regency and as a reference for recommendations for land management in accordance with nutrient status and fertility levels in the three uses. different lands in Dolo District, Sigi Regency. This research was conducted in Langaleso Village and Kabobona Village, Dolo District, Sigi Regency, taking soil samples on cocoa land, deep coconut land and dry land in Dolo District, Sigi Regency. This type of research is a survey method and the data is presented descriptively. By trying to conduct observational surveys and soil sampling by purposive sampling. Soil samples were taken from 3 types of land use, namely cocoa land (K), Kelapa Dalam land (P) and dry land (T). Soil samples were taken at a depth of 0 - 20 cm and 21 - 40 cm. Where each land use is taken at two different locations, each two points of soil sampling and composited so that a total of 12 soil samples are obtained. The results of the research showed that the nutrient status that became an obstacle in soil fertility in Dolo District, Sigi Regency was Soil Reaction (pH) slightly acidic, Cation Exchange Capacity (CEC), C-organic, Nitrogen (N), Phosphorus (P), Potassium ( K) is classified as moderate, and base saturation (KB) is low so that the level of soil fertility on coconut, cocoa and dry fields in Dolo District, Sigi Regency is moderate and has unhealthy/less fertile soil quality.